1982
DOI: 10.1002/pssa.2210720121
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth and Spectroscopic Properties of Nd3+ Ions in Ferroelectric Pb5Ge3O11 Crystals

Abstract: Single crystals of ferroelectric lead germanate Pb5Ge3O11 doped with neodymium are grown. Absorption and luminescence spectra and luminescence lifetime are investigated at 77 and 300 K. The spectra are assigned to the crystal field splitting of manifolds. Intermanifold branching ratios and cross‐sections of transitions are calculated using the luminescence parameter Y and the spectroscopic quality parameter X. The possibility of stimulated emission is anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Anomalous hump at transition temperature is another significant observation (Goto and Sawaguchi 1979;Mansingh et al 1979;Dhuley and Katpatal 1985). Kaminskii et al (1982) predicted Nd +3 to enter one or more Pb sites because of similar ionic radii of Pb + 2 and Nd + 3. Moiseenko et al (1985) also reported replacement of Pb ion with La and Bi in lead germanate single crystal.…”
Section: Introductionmentioning
confidence: 99%
“…Anomalous hump at transition temperature is another significant observation (Goto and Sawaguchi 1979;Mansingh et al 1979;Dhuley and Katpatal 1985). Kaminskii et al (1982) predicted Nd +3 to enter one or more Pb sites because of similar ionic radii of Pb + 2 and Nd + 3. Moiseenko et al (1985) also reported replacement of Pb ion with La and Bi in lead germanate single crystal.…”
Section: Introductionmentioning
confidence: 99%